Predicting financial distress in property and real estate companies: moderation of company size - Saraswati, Wiwik (LPPM ISNJ Bengkalis, 2025)
Purpose – This study analyses the effect of intellectual capital, return on assets (ROA), and debt-to-equity ratio (DER) on financial distress moderated by company size. Method – This study uses a quantitative method using secondary data from publications obtained through the Indonesia Stock Exchange (IDX) official website. The research population comprises real estate and property companies listed on the IDX 2018–2023. The sampling technique uses the purposive sampling method so that 90 observation data are obtained from 15 property and real estate companies as samples. The data analysis techniques utilized are panel data regressions and moderated regression analysis (MRA) using EViews 12. As a result of Chow and Hausman's tests, the random effect model is the selected model. Findings – The study findings indicate that DER, ROA, intellectual capital and company size positively affect financial distress. Company size can strengthen the influence of ROA and intellectual capital on financial distress. However, it cannot moderate DER and financial distress. Implications – The research findings contribute to the scientific understanding of financial distress determinants in property and real estate companies. The practical implication of these findings is that the company must sustainably increase investor trust by maintaining the company's good performance in the stock exchange.